Evaluation of wheat genotypes for heat stress tolerance and identification of early stress indicators - Chileshe, P.; Chikuta, S.; Lungu, D.; Kamfwa, K.; Omondi, J.O. (Springer, 2023)
Heat stress is an abiotic factor that reduces wheat yields. This study assessed the morphological and physiological traits essential for early detection of heat tolerance in wheat and identified suitable genotypes for specific agro-ecologies prone to heat stress in Zambia. Twelve wheat genotypes were evaluated in a heat-stress environment (Chakanka) and a non-stress heat environment (UNZA). Early heat stress indicators like leaf thickness and chlorophyll content had a 92% and 90% relationship with the yields of heat-tolerant genotypes, respectively. An increase in either or both parameters improved the yields of heat-tolerant genotypes relative to the susceptible ones. Among the heat-tolerant genotypes, Entry 48 had the highest yield (5866.5 kg ha−1) at the heat-stress site; this yield was 51.2% higher than that of the most susceptible genotype, Kwale (2864.0 kg ha−1). Entry 48 was more adapted to heat stress and yielded better than others due to early flowering (53.8 days to 50% flowering) and longer grain-filling duration (40.3 days). Entry 48 possessed traits of a climate-smart variety and could be a candidate for breeding future heat-tolerant and high-yielding wheat varieties.